The little wartime library - Thompson, Kate (Hodder & Stoughton, 2022)
London, 1944. Clara Button is no ordinary librarian. While the world remains at war, in east London Clara has created the country's only underground library, built over the tracks in the disused Bethnal Green tube station. Down here a whole community thrives: with thousands of bunk beds, a nursery, a café and a theatre offering shelter, solace and escape from the bombs that fall above. Along with her glamorous best friend and library assistant Ruby Monroe, Clara ensures the library is the beating heart of life underground. But as the war drags on, the women's determination to remain strong in the face of adversity is tested to the limits when it seems it may come at the price of keeping those closest to them alive.
Keywords: Button, Clara : (fiktiivinen hahmo); Munroe, Ruby : (fiktiivinen hahmo); ystävyys; toinen maailmansota; kirjastonhoitajat; naiset; kirjastot; maanalaiset tilat; sota-aika; Lontoo; Iso-Britannia